Initial teacher educators' integrating iPads into their physical education teaching. Issue 4 (2nd October 2021) - Marron, Susan; Coulter, Maura
Abstract : Teachers today must not only be prepared to use technology but must also know how to use it (Butler, D., K. Marshall, and M. Leahy. 2015. Shaping the Future: How Technology Can Lead to Educational Transformation, 1st ed . Dublin: Liffey Press). The purpose of this study was to explore two primary physical education initial teacher educator's (PEITE's) professional learning experiences while introducing iPads into a physical education module. The module's focus was to promote quality teaching, learning and assessment of fundamental movement skills in physical education with pre-service generalist primary teachers. It was a qualitative study utilising lesson study methodology. Data included audio files, video recordings and field notes. Following analysis, three themes were developed: learning the technology, managing the technology and integrating the technology. The findings showed that for the PEITEs, time was a valuable commodity while grappling with technological knowledge, technological pedagogical knowledge and pre-service teachers' physical education knowledge. Self-directed learning was an enabler to facilitate technological and pedagogical competence for the PEITEs. Although managing aspects of the technology, such as limited Wi-Fi access and technical support, was a challenge, the PEITEs continued to integrate iPads into their teaching.